2020
DOI: 10.1186/s12870-020-02776-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of long sterile lemma (lsl2), a single recessive gene that regulates spike germination in rice (Oryza sativa L.)

Abstract: Background Rice is a typical monocotyledonous plant and an important cereal crop. The structural units of rice flowers are spikelets and florets, and floral organ development and spike germination affect rice reproduction and yield. Results In this study, we identified a novel long sterile lemma (lsl2) mutant from an EMS population. First, we mapped the lsl2 gene between the markers Indel7–22 and Indel7–27, which encompasses a 25-kb region. The ric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Although many lines of evidence support the inference that these are sterile lemmas, they are expanded bracts without an axillary meristem so share some characteristics with glumes. Mutations in G1 / LONG SLENDER LEMMA1 ( Yoshida et al, 2009 ; Yang et al, 2020 ) shift the size and cellular morphology of the sterile lemmas to look more like true lemmas, whereas mutations in other genes lead to stronger similarity between the sterile lemmas and rudimentary (true) glumes (summarized by Ren et al, 2018 ; Xu et al, 2020) . However, none of the mutants leads to production of an axillary FM, as would be expected if the sterile lemmas were fully converted to true lemmas.…”
Section: Spikelet Bracts (Glumes) Expand Axillary Bud Growth Is Suppr...mentioning
confidence: 99%
“…Although many lines of evidence support the inference that these are sterile lemmas, they are expanded bracts without an axillary meristem so share some characteristics with glumes. Mutations in G1 / LONG SLENDER LEMMA1 ( Yoshida et al, 2009 ; Yang et al, 2020 ) shift the size and cellular morphology of the sterile lemmas to look more like true lemmas, whereas mutations in other genes lead to stronger similarity between the sterile lemmas and rudimentary (true) glumes (summarized by Ren et al, 2018 ; Xu et al, 2020) . However, none of the mutants leads to production of an axillary FM, as would be expected if the sterile lemmas were fully converted to true lemmas.…”
Section: Spikelet Bracts (Glumes) Expand Axillary Bud Growth Is Suppr...mentioning
confidence: 99%
“…In adult rice plants, PS‐NPs were also detected in spikes by SEM and laser confocal microscope (Figure S7, Supporting Information), whose germination is an important factor affecting the yield and processing quality of rice grain. [ 33 ] Ten days after flowering, the husk of immature rice grains in the grouting period was removed, and the liquid starch was subjected to fluorescence imaging. Nanoplastics entered the grain at the early grain‐setting stage of rice (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis revealed that mutation was occurred in highly conserved site and have been reported in maize, sorghum and rice [1,49]. This site can be targeted by molecular breeder to solve the specific problem of germination in hybrid rice [51]. Protein of this site may have specific binding activity to some other genes that regulate different traits including the development of lemma [48].…”
Section: Asp-lsl Encodes a Single Recessive Nuclear Transactional Repressor Genementioning
confidence: 98%
“…Most of them are homologous to Arabidopsis and have a certain degree of conservation. These findings provide a basis for studying more about the regulation mechanism of rice flower development, without disturbing other major agronomic yield traits [51,52]. In grasses, these homologous proteins can interact with ETHYLENE RESPONSE FACTOR (ERF), Jasmonic acid (JA), and IAA [47,49].…”
Section: Asp-lsl Encodes a Single Recessive Nuclear Transactional Repressor Genementioning
confidence: 99%